Prospective Swiss pilot study of Endocuff-assisted colonoscopy in a screening population - Sawatzki, Mikael; Meyenberger, Christa; Marbet, Urs Albert; Haarer, Johannes; Frei, Remus (Endoscopy International Open, 2015)
Background and study aims: The adenoma detection rate (ADR) is one of the quality measures in screening colonoscopy and is crucial for reducing colorectal cancer morbidity and mortality. Up to 25 % of adenomas are missed during colonoscopy. Endocuff is an easy-to-use device that is attached like a cap to the distal tip of the colonoscope in order to optimize visualization behind the folds of the colon and increase the ADR. This is the first prospective study of Endocuff-assisted colonoscopy (EC) in a screening population with follow-up to determine the ADR and adverse events of EC.Patients and methods: We prospectively enrolled asymptomatic patients referred for screening colonoscopy during the 4-month study period. We documented the Boston Bowel Preparation Scale (BBPS) score, cecal intubation rate, polyp detection rate, ADR, number of advanced adenomas, and number of adverse events. Colonoscopies were performed by five board-certified gastroenterologists. During follow-up, the patients were called 4 to 12 weeks after EC.Results: A total of 104 EC procedures were performed. Cecal intubation was achieved in 99 % of the patients, with a median intubation time of 6 minutes. The polyp detection rate and ADR in our study were 72 % and 47 %, respectively, and 13.5 % of the lesions were advanced adenomas. A significant number of adenomas were detected in the right side of the colon. Considering all the adenomas and hyperplastic polyps above the sigmoid, we recommended that nearly 60 % of our patients repeat an endoscopic follow-up according to the existing Swiss guidelines. We noted no perforations or other serious adverse events, even in the patients with extensive diverticulosis. Conclusions: EC is feasible with the most commonly available colonoscopes without severe adverse events. EC seems to be a safe and effective device for increasing the ADR, including small adenomas in the right side of the colon. Therefore, this technique may be recommended in the future to increase the ADR in a screening population.